2017
DOI: 10.1002/1873-3468.12636
|View full text |Cite
|
Sign up to set email alerts
|

A farnesoic acid‐responsive transcription factor, Hot1, regulates yeast‐hypha morphogenesis in Candida albicans

Abstract: Candida albicans hyphal formation is inhibited by a quorum-sensing molecule, farnesoic acid, which accumulates in the medium as the cells proliferate. We recently showed that Pho81 is essential for the inhibition of hyphal growth by farnesoic acid. Here, we describe a newly identified regulator, Hot1, which increases the expression of PHO81. The binding site of Hot1 in the PHO81 promoter region was identified by DNase I protection assay. The hot1Δ mutant grows extensively as filaments. Furthermore, the inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The pho81Δ mutant cells existed exclusively as filaments and were insensitive to inhibition by FA. Second, the mRNA abundance of HOT1 and PHO81 increased dramatically between 40 and 240 min following treatment with FA, but remained unchanged following treatment with FOH [6]. Similar to the pho81Δ strain from their previous work, the hot1Δ mutant cells grew exclusively as filaments and were insensitive to FA inhibition of hyphal morphogenesis.…”
supporting
confidence: 66%
See 4 more Smart Citations
“…The pho81Δ mutant cells existed exclusively as filaments and were insensitive to inhibition by FA. Second, the mRNA abundance of HOT1 and PHO81 increased dramatically between 40 and 240 min following treatment with FA, but remained unchanged following treatment with FOH [6]. Similar to the pho81Δ strain from their previous work, the hot1Δ mutant cells grew exclusively as filaments and were insensitive to FA inhibition of hyphal morphogenesis.…”
supporting
confidence: 66%
“…Pho81p was identified as a cyclin-dependent kinase inhibitor, and its activation by phosphate-limiting conditions leads to a decrease in Pho80/Pho85 activity, leading to dephosphorylation and activation of Pho4. If we assume that it is the hypophosphorylated, nuclear-localized form of Pho4p that is active in the regulation of filamentation, this raises a conflict with the data presented by Chung et al [8] and Ahn et al [6]. Pho4p is a basic helix-loop-helix transcription factor that binds to and activates genes involved with phosphate acquisition and polyphosphate mobilization, and the work of Ikeh et al [12] showed that a pho4Δ mutant strain fails to form hyphal germ tubes under hyphae-inducing conditions.…”
Section: An Apparent Paradox In the Regulation Of Hyphal Morphogenesimentioning
confidence: 75%
See 3 more Smart Citations